2012
DOI: 10.1111/j.1365-2249.2012.04590.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ficolin-2 and ficolin-3 in normal pregnancy and pre-eclampsia

Abstract: SummaryFicolins are soluble molecules of the innate immune system that recognize carbohydrate molecules on microbial pathogens, apoptotic and necrotic cells. They act through two distinct routes: initiating the lectin pathway of complement activation and mediating a primitive opsonophagocytosis. In this study, we measured plasma levels of ficolin-2 and ficolin-3 in 60 pre-eclamptic patients, 60 healthy pregnant women and 59 healthy non-pregnant women by enzyme-linked immunosorbent assay (ELISA). Circulating le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Ficolin-3 binds to GlcNAc, Nacetyl-galactosamine (GalNAc) and fucose [39]. Preeclamptic patients had significantly lower ficolin-2 and ficolin-3 concentrations than healthy non-pregnant and pregnant women [40]. Recently, research showed that plasma ficolin-3, a kind of soluble PRR within the lectin pathway varied significantly between individuals with NGT and those with T2DM [41].…”
Section: Discussionmentioning
confidence: 98%
“…Ficolin-3 binds to GlcNAc, Nacetyl-galactosamine (GalNAc) and fucose [39]. Preeclamptic patients had significantly lower ficolin-2 and ficolin-3 concentrations than healthy non-pregnant and pregnant women [40]. Recently, research showed that plasma ficolin-3, a kind of soluble PRR within the lectin pathway varied significantly between individuals with NGT and those with T2DM [41].…”
Section: Discussionmentioning
confidence: 98%
“…Ficolin-2 has been recently shown to be important during pneumococcal pathogenesis (2)(3)(4) and is known to bind to many other significant human pathogens (2,5,6). Moreover, ficolin-2 and -3 have been implicated in many different disease pathologies, such as transplant reperfusion injury (7), clearance of apoptotic cells (8,9), and even preeclampsia (10).…”
mentioning
confidence: 99%
“…Crystallography studies have shown that ficolin-1 and ficolin-3 have only one binding pocket each, while ficolin-2 has four binding pockets, which may make it a more promiscuous binder (4). Ficolin-2 is known to bind many acetylated ligands (5) and various biological ligands, such as apoptotic cells (6), and may be important in renal transplantation (7) and preeclampsia (8). It also binds to several significant human pathogens, like group B streptococcus (9) and Salmonella enterica serovar Typhimurium (10), and to many Gram-positive bacterial teichoic acids (11).…”
mentioning
confidence: 99%